Status Singing in Uzbek Music - Javokhirkhoja Sodiqhkojaugli Kayumov (Zien Journals, 2023)
The art of status in Uzbek music performance has been surprising listeners with its mysterious world since time immemorial. Voice interpretation, musical performance, and human qualities have been passed down over time as important factors in Maqom's solo singing. In the past, khans in voice interpretation, that is, the field of singing, was formed and developed in different directions and styles. Based on this, in the form of voice interpretation, the unique values, dialect and life traditions of each nation and people are expressed in their songs.
Keywords: music; Musical education; songs